The calcium sensor CBL7 is required for Serendipita indica‐induced growth stimulation in Arabidopsis thaliana, controlling defense against the endophyte and K+ homoeostasis in the symbiosis. (29th August 2022) - Pérez‐Alonso, Marta‐Marina; Guerrero‐Galán, Carmen; González Ortega‐Villaizán, Adrián; Ortiz‐García, Paloma; Scholz, Sandra S.; Ramos, Patricio; Sakakibara, Hitoshi; Kiba, Takatoshi; Ludwig‐Müller, Jutta; Krapp, Anne; Oelmüller, Ralf; Vicente‐Carbajosa, Jesús; et al.
Abstract: Calcium is an important second messenger in plants. The activation of Ca 2+ signalling cascades is critical in the activation of adaptive processes in response to environmental stimuli. Root colonization by the growth promoting endophyte Serendipita indica involves the increase of cytosolic Ca 2+ levels in Arabidopsis thaliana . Here, we investigated transcriptional changes in Arabidopsis roots during symbiosis with S. indica . RNA‐seq profiling disclosed the induction of Calcineurin B‐like 7 ( CBL7 ) during early and later phases of the interaction. Consistently, reverse genetic evidence highlighted the functional relevance of CBL7 and tested the involvement of a CBL7‐CBL‐interacting protein kinase 13 signalling pathway. The loss‐of‐function of CBL7 abolished the growth promoting effect and affected root colonization. The transcriptomics analysis of cbl7 revealed the involvement of this Ca 2+ sensor in activating plant defense responses. Furthermore, we report on the contribution of CBL7 to potassium transport in Arabidopsis. We analysed K + contents in wild‐type and cbl7 plants and observed a significant increase of K + in roots of cbl7 plants, while shoot tissues demonstrated K + depletion. Taken together, our work associates CBL7 with an important role in the mutual interaction between Arabidopsis and S. indica and links CBL7 to K + transport.